2011
DOI: 10.3389/fpsyg.2011.00309
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Expertise in Simultaneous Interpreting on Non-Verbal Executive Processes

Abstract: This study aimed to explore non-verbal executive processes in simultaneous interpreters. Simultaneous interpreters, bilinguals without any training in simultaneous interpreting, and control monolinguals performed the Wisconsin card sorting task (WCST; Experiment 1) and the Simon task (Experiment 2). Performance on WCST was thought to index cognitive flexibility while Simon task performance was considered an index of inhibitory processes. Simultaneous interpreters outperformed bilinguals and monolinguals on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
168
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(194 citation statements)
references
References 68 publications
17
168
2
7
Order By: Relevance
“…In cued switching paradigms, there is some indication that the daily experience of language switching may impact asymmetries, such that participants who frequently switch languages in their daily lives show reduced switch costs (e.g., Prior & Gollan, 2011;Christoffels et al, 2007). Evidence from simultaneous interpreters further suggests that language experience influences control processes (e.g., Ibá ñ ez, Macizo, & Bajo, 2010;Yudes, Macizo, & Bajo, 2011). We also now know that codeswitching is grammatical and that the cost of codeswitching is small relative to what might be predicted and in comparison to cued language switching (e.g., Chan, Chau, & Hoosain, 1983;Dussias, 2003;Guzzardo Tamargo, 2012;Moreno, Federmeier, & Kutas, 2002).…”
Section: Resultsmentioning
confidence: 95%
“…In cued switching paradigms, there is some indication that the daily experience of language switching may impact asymmetries, such that participants who frequently switch languages in their daily lives show reduced switch costs (e.g., Prior & Gollan, 2011;Christoffels et al, 2007). Evidence from simultaneous interpreters further suggests that language experience influences control processes (e.g., Ibá ñ ez, Macizo, & Bajo, 2010;Yudes, Macizo, & Bajo, 2011). We also now know that codeswitching is grammatical and that the cost of codeswitching is small relative to what might be predicted and in comparison to cued language switching (e.g., Chan, Chau, & Hoosain, 1983;Dussias, 2003;Guzzardo Tamargo, 2012;Moreno, Federmeier, & Kutas, 2002).…”
Section: Resultsmentioning
confidence: 95%
“…Evidence points towards advantages on working memory (Christoffels et al, 2006;Daró and Fabbro, 1994;Fabbro and Daró, 1995;Kopke and Nespoulous, 2006;Stavrakaki et al, 2012;Yudes et al, 2011Yudes et al, , 2012, and on some aspects of cognitive control, such as cognitive flexibility (Yudes et al, 2011). Little work exists on linguistic-processing differences between interpreters and non-interpreter multilinguals, although one EEG study has reported different cross-linguistic semantic priming effects in professional interpreters comparing to proficiency-matched L2 speakers (Elmer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Interpreting training, with this higher demand, may thus enhance the efficiency of language control and eventually transfers to non-verbal tasks. Yudes, Macizo, and Bajo (2011) found that professional simultaneous interpreters outperformed control bilinguals and monolinguals in the cognitive control function of mental flexibility. In their study, a Simon task (which tested inhibition) and a Wisconsin Card Sorting Test (WCST) (which tested shifting) were adopted.…”
mentioning
confidence: 98%